CCAFS Science Strengthens Investments in Climate Services for Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Climate services are highly practical tools, improving farmer decision-making and strengthening their ability to cope with increased climate variability and extreme weather events. By providing climate advisories and weather forecasts, these services enhance farmers’ capacity to deal with risk. Through research and stakeholder engagement, CCAFS informed and shaped investments into climate services, building the capacity and know-how of agencies and organisations tasked with getting the information out to farmers. These investments, totaling approximately USD 16 million, include: - USD 10 million investment by the Norwegian Agency for Development Cooperation (Norad) in a multi-sector national implementation project in Tanzania and Malawi, under the UN Global Framework for Climate Services (GFCS) - World Bank investment in agrometeorological services in Myanmar - USAID investment in climate-services through a small grants initiative designed by CCAFS